(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2015)
The main aim of this work is to study dynamics of plasma current sheath, PCS during the axial acceleration phase in term of its axial velocity, Vz and the induced azimuthal magnetic field induction, BÎ¸ in 2.2 KJ plasma focus, PF device of Mather type. It powered by a capacitor bank of 30 µf capacity with charging voltage of 12 KV. In the present paper all the experimental work are performed for Argon gas pressure in the range of 0.2 1.8 Torr. The length of the inner electrode, IE has been changed to 9.5, 10.5 and 11.5 cm respectively. To detect, BÎ¸ and Vz three identical magnetic probes are located at radial distance r1 = 2.75 cm, r2 = 3.5 cm and r3 = 4.25 cm from the IE axis and at axial distance z = 8.15 cm from coaxial electrodes breech.The dependence of Vz and BÎ¸ on gas pressures are measured and the results of them clear that, Vz is decayed with increasing of gas pressures and it has a maximum value for IE length of 10.5 cm, P = 0.2 Torr and at r1, while BÎ¸ has a maximum value for IE length = 11.5 cm, 1.2 Torr at r1 . Also distribution of Vz with p in linear fitting shows that efficient a snow-plough action is obtained approximately for IE length = 10.5 cm. Results of Vz versus radial distance demonstrated that the PCS has a parabolic shape especially at lower Argon gas pressures. Results of modification factor, F as a function of gas pressures show that at IE = 10.5 cm, r1 and for most Argon gas pressures F has a higher values than any others IE lengths and radial distances. Also the decay of dF/dp along radial distances has a smaller values at IE length = 11.5 cm than any other lengths (9.5 and 10.5 cm).